An organic transistor for the selective detection of tropane alkaloids utilizing a molecularly imprinted polymer. Issue 35 (11th July 2022) - Zhou, Qi; Sasaki, Yui; Ohshiro, Kohei; Fan, Haonan; Montagna, Valentina; Gonzato, Carlo; Haupt, Karsten; Minami, Tsuyoshi
Abstract : An organic transistor functionalized with a molecularly imprinted polymer (MIP) succeeded in the highly selective detection of chiral tropane alkaloids owing to the optimized internal molecular recognition sites in the MIP. Abstract : This study proposes a chemical sensing approach for the selective detection of tropane alkaloid drugs based on an extended-gate-type organic field-effect transistor (OFET) functionalized with a molecularly imprinted polymer (MIP). From the viewpoint of pharmaceutical chemistry, the development of versatile chemical sensors to determine the enantiomeric purity of over-the-counter (OTC) tropane drugs is important because of their side effects and different pharmacological activities depending on their chirality. To this end, we newly designed an OFET sensor with an MIP (MIP-OFET) as the recognition element for tropane drugs based on a high complementarity among a template ( i.e., ( S )-hyoscyamine) and functional monomers such as N -isopropylacrylamide and 2, 2-dimethyl-4-pentenoic acid. Indeed, the MIP optimized by density functional theory (DFT) has succeeded in the sensitive and selective detection of ( S )-hyoscyamine (as low as 1 μM) by the combination of the OFET with highly selective recognition sites in the MIP. The MIP-OFET was further applied to determine the enantiomeric excess (ee) of commercially available ( S )-hyoscyamine, and the linearity changes in the threshold voltages of the OFET corresponded to the % ee values of ( S )-hyoscyamine. Overall, the validation with tropane alkaloids revealed the potential of the MIP combined with OFET as a chemical sensor chip for OTC drugs in real-world scenarios.